2021
DOI: 10.1186/s13550-021-00764-z
|View full text |Cite
|
Sign up to set email alerts
|

The joint use of 99mTc-MAA-SPECT/CT and cone-beam CT optimizes radioembolization planning

Abstract: Purpose To determine which imaging method used during radioembolization (RE) work-up: contrast-enhanced computed tomography (CECT), 99mTc-MAA-SPECT/CT or cone beam-CT (CBCT), more accurately predicts the final target volume (TgV) as well as the influence that each modality has in the dosimetric calculation. Methods TgVs from 99mTc-MAA-SPECT/CT, CECT and CBCT were consecutively obtained in 24 patients treated with RE and compared with 90Y PET/CT TgV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…In addition to 166 Ho-and 90 Y-microspheres SPECT/CT, conebeam CT (CBCT) represents a promising tool for the definition of 3 D vascular anatomy and the evaluation of non-target embolization during pre-treatment angiography and is used in many centres [40][41][42][43]. CBCT visualises segmental perfusion and can be used to improve the positioning of the catheter for optimal tumour coverage during intra-arterial therapy [44].…”
Section: Patient Selection and Treatment Planning For Radioembolizationmentioning
confidence: 99%
“…In addition to 166 Ho-and 90 Y-microspheres SPECT/CT, conebeam CT (CBCT) represents a promising tool for the definition of 3 D vascular anatomy and the evaluation of non-target embolization during pre-treatment angiography and is used in many centres [40][41][42][43]. CBCT visualises segmental perfusion and can be used to improve the positioning of the catheter for optimal tumour coverage during intra-arterial therapy [44].…”
Section: Patient Selection and Treatment Planning For Radioembolizationmentioning
confidence: 99%
“…Currently, the technology available in most centers performing TARE, comprising the incorporation of cone beam CT (CBCT), SPECT/CT gamma cameras and the design of dedicated software for voxel-based multicompartment dosimetric analysis, allows for much safer planning of the procedure and the implementation of highly personalized therapies [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Gordic et al have shown that for dual-energy CT the contrast enhancement at a specific time point correlates strongly with arterial perfusion, a metric that was normally extracted from a dynamic CT scan with 16 temporal frames. 17 Timed CE interventional cone-beam CT (CBCT) is already routinely and widely used for the determination of the optimal injection site and perfusion territories, [18][19][20][21][22] making this a good candidate for prospective treatment planning.…”
Section: Introductionmentioning
confidence: 99%